2014
DOI: 10.1242/jcs.148056
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of GPI-anchored proteins from yeast to mammals – common pathways at different sites?

Abstract: Glycosylphosphatidylinositol (GPI)-anchored proteins (GPI-APs) are luminal secretory cargos that are attached by a post-translational glycolipid modification, the GPI anchor, to the external leaflet of the plasma membrane. GPI-APs are conserved among eukaryotes and possess many diverse and vital functions for which the GPI membrane attachment appears to be essential. The presence of the GPI anchor and its subsequent modifications along the secretory pathway confer to the anchored proteins unique trafficking pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 105 publications
(117 reference statements)
0
68
0
2
Order By: Relevance
“…Mechanisms of apical sorting of GPI-APs have been intensively studied ( 10 ). Oligomerization of GPI-APs in the trans-Golgi network seems to be critical for selective transport to the apical surface [see detailed discussion in a recent review ( 82,83 )]. …”
Section: Diacyl To Alkyl-acyl Lipid Remodelingmentioning
confidence: 99%
“…Mechanisms of apical sorting of GPI-APs have been intensively studied ( 10 ). Oligomerization of GPI-APs in the trans-Golgi network seems to be critical for selective transport to the apical surface [see detailed discussion in a recent review ( 82,83 )]. …”
Section: Diacyl To Alkyl-acyl Lipid Remodelingmentioning
confidence: 99%
“…In addition, proteomic analysis of sterol-enriched detergent-resistant membranes in Arabidopsis revealed that GPI-APs are overrepresented in those membranes (Kierszniowska et al, 2009). Indeed, more detailed studies in mammalian cells show that an association with membrane microdomains is a general property of GPI-APs; however, the pattern of their lateral organization at the cell surface is determined by additional signals associated with protein ectodomain, cell type, and physiological state (Muñiz and Zurzolo, 2014;Paladino et al, 2015;Saha et al, 2016). Expression of BG_pap and PDCB1 with their ectodomains resulted in a higher accumulation at Pd, but not at the PM, compared with GPI-anchored mCitrine (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…7), which again indicates that Pd exclusion most likely occurs prior to PM and Pd localization. Studies in mammalian cells have shown that the sorting of different groups of GPI-APs occurs at the trans-Golgi network (TGN; Muñiz and Zurzolo, 2014). In polarized human and Madin-Darby canine kidney epithelial cells, the GPI-APs that target to the microdomain-rich apical PM segregate from the basolateral GPI-APs by forming large microdomain-rich clusters at the TGN (Muñiz and Zurzolo, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations